PERANCANGAN SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN KAS PADA UD. ENDA TANI BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL - Felisa Deswana Sianturi; Rena Nainggolan; Duma Megaria Elisabeth (Universitas Methodist Indonesia, 2022)
One of the fields where science and information technology has experienced rapid progress is in the business world. The pace of technological progress is getting faster, demanding the economic sector to follow too. This is especially true for the needs of agricultural businesses, considering that today's business management techniques by utilizing digital media are increasingly effective and efficient. UD. Enda Tani is a private company engaged in the field of agricultural equipment and tools. Still using a manual system in running their business and have not switched to using a digital system. Enda Tani will develop a web-based cash receipts and disbursement information system by utilizing the Laravel framework and MySQL database to improve UD's performance. The system created will be able to produce customer data, inventory data, expired goods data, cash receipts, and disbursement transaction processing data and can make reports simpler and more effective, present accurate, relevant, and timely information, and can facilitate transactions from customers to UD. Enda Tani with computerization. The author uses observation and interviews to compile the requirements needed for information system design at UD Enda Tani. In addition, the authors use database and interface design to create a system for making cash receipts and disbursements information systems.